New fossils of Alcelaphini and Caprinae (Bovidae: Mammalia) from Awash, Ethiopia, and phylogenetic analysis of Alcelaphini - Vrba, E. S. (Bernard Price Institute for Palaeontological Research, 1997)
Alcelaphine antelopes comprise one of the most species-rich groups among the mammalian assemblages from the Middle Awash, Ethiopia, and in Africa as a whole. I describe a new genus and species Awashia suwai from Matabaietu 3, and other new alcelaphine species, Damaliscus ademassui from Gamedah I and Beatragus whitei from Matabaietu 3-5, all dated ca. 2.5 m.y. (millions of years). Other new a lcelaphine fossils from Middle Awash include an Early Pliocene species allied to Damalops, Late Pliocene records of Parmularius c f.pandatus and Beat rag us amiquus, and Middle Pleistocene records of Megalotragus kattwinkeli, P. angusticornis, Damaliscus niro, Connochaetes taurinus olduvaiensis, Numidocapra crassicornis, and Alcelaphus buselaphus. My comparisons of these fossils with all other known fossil and Recent Alcelaphini inc ludes a cladistic analysis . The results suggest that during or before the Miocene-Pliocene transition two alcelaphine subtribes dive rged for which I suggest the names Alcelaphina and Damaliscina. Alcelaphina consists of two ancient subclades: ( I) the s is te r-group of Damalacra neanica and Beatragus known since 5.0-4.5 m.y. ago, and (2) a large c lade first recorded 4.4 m.y. ago (genera Damalops, Numidocapra, Alce/aphus, Rabaticeras, Megalotragus, Oreonagor, and Connochaetes) that had a high diversification rate since 3 m.y. ago. The earliest record of Damaliscina is the form that Gentry ( 1980) named Damalacra acalla, which emerges as the hypothetical direct ancestor of the Early-Middle Plioce ne split into Parmularius and the Damaliscus group. The placement of the new genus Awashia remains problematic. A new ov ibovine genus and spec ies, Nitidarcus asfawi, and a new caprine genu and species, Bouria anngettyae, both from Bouri I, are also described. I discuss some evolutionary and biogeographic implications of the new fossils from Middle Awash.
Main article
Keywords: Alcelaphini, Caprinae, Awash, Ethiopia